EFFICACY OF NINE CROATIAN INERT DUSTS AGAINST RICE WEEVIL SITOPHILUS ORYZAE L. (COLEOPTERA: CURCULIONIDAE) ON WHEAT - Liška, Anita; Korunić, Zlatko; Rozman, Vlatka; Halamić, Josip; Galović, Ines; Lucić, Pavo; Baličević, Renata (Emirates Journal of Food and Agriculture, 2017)
Laboratory bioassay was carried out to study the insecticidal effect of 9 Croatian inert dusts against Sitophilus oryzae (L.) and to test their influence on bulk density of treated wheat. In order to compare effectiveness of Croatian inert dust samples, a standard USA diatomaceous earth (DE) Celatom® Mn 51, registered as an insecticide for stored-products protection, was used. Wheat kernels with approximately 13% moisture content were treated with inert dusts at doses 300, 400, 500 and 600 ppm and mortality of S. oryzae adults was assessed after 7 and 14 days and progeny after 49 days. The most effective Croatian inert dust samples were D-02B, D-01 and MA-4 with the LD90 values of 359.6, 447.2 and 458.7 ppm, respectively. In addition, effective dose that reduced F1 progeny in half was lower in regard to the other tested samples including the standard DE Mn 51, with the ED50 values 71.9, 54.6 and 137.6 ppm, respectively. According to the XRF analytical results, the highest amount of biogenic silica (BSi) was found in samples D-02B, D-01 and MA-4 (45.98, 35.09 and 21.28%, respectively). Paleontological data analysis confirmed diatoms species in only 5 samples of Croatian inert dusts (D-01, D-02B, PD-1, MA-4 and JU-1). All tested inert dusts affected reduction in bulk density of treated wheat at the LD90 concentrations, from 4.4 (D-02B) to 5.6 (JU-1) kg hL-1. More effective inert dusts at lower doses equally reduced bulk density as less effective inert dusts at much higher doses.